1975
DOI: 10.1037/h0076337
|View full text |Cite
|
Sign up to set email alerts
|

Self-discrimination responses in black school children.

Abstract: Previous studies found that the performance of blacks on intellectual tasks decreases in the presence of whites. This study attempted to determine if this performance decrement still exists by administering three trials of a digit symbol task to black junior high school students in the presence of either white or Negro counselors. The task was labeled as either intellectual or motor skill. In addition, measures of expectancy, incentive, anxiety, hostility, defensiveness, and task satisfaction were obtained. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…All groups of subjects, regardless of race or sex, scored higher in IQ in the presence of a white tester, a finding which does not come as a total surprise given the literature reviewed earlier. Sappington and Grizzard (1975) have similarly reported that white experimenters were more effective than black experimenters in eliciting maximal performance from black junior high school students on a digit symbol test. The score advantage of students tested by white experimenters was most pronounced when the task was described as a test of intelligence rather than of motor skills.…”
Section: Discussionmentioning
confidence: 92%
“…All groups of subjects, regardless of race or sex, scored higher in IQ in the presence of a white tester, a finding which does not come as a total surprise given the literature reviewed earlier. Sappington and Grizzard (1975) have similarly reported that white experimenters were more effective than black experimenters in eliciting maximal performance from black junior high school students on a digit symbol test. The score advantage of students tested by white experimenters was most pronounced when the task was described as a test of intelligence rather than of motor skills.…”
Section: Discussionmentioning
confidence: 92%